Metabolomic profile combined with transcriptomic analysis reveals the value of UV-C in improving the utilization of waste grape berries. (30th November 2021) - Zhang, Kekun; Chen, Li; Wei, Mengyuan; Qiao, Haorong; Zhang, Shihao; Li, Zhihao; Fang, Yulin; Chen, Keqin
Graphical abstract: Highlights: UV-C promotes the accumulation of stilbenes and some flavonoids in waste grape berries at each developmental stage. UV-C activates the phenolic compounds biosynthesis pathways in immature berries. UV-C modulates the metabolomic and transcriptomic profile of waste grape berries. Abstract: Table grape is a popular fruit worldwide. The quality of the appearance of table grapes directly affects their commercial value. Table grape bunches are usually carefully managed during production. At different developmental stages, a large number of grape berries are pruned as waste for commercial appearance, which leads to wasted resources. Ultraviolet-C (UV-C) can regulate the accumulation of secondary metabolites in fruits. In this study, metabolomic profile was combined with transcriptomic analysis technology to explore the value of UV-C in improving the utilization of waste grapes. The berries of the 'Jumeigui' grape were subjected to UV-C radiation treatment in the green-berry stage, veraison stage, and maturation stage. The results showed that UV-C could brown grape berries and decrease their sugar content at different developmental stages. Compared with other samples, those treated with UV-C in the veraison stage had the most upregulated metabolites, while samples in the green-berry stage had the most down-regulated metabolites. UV-C promoted the accumulation of stilbenes and some flavonoids in the berries at each developmental stage (especially at the green-berry and veraison stages). Compared with other stages, UV-C treatment during the veraison stage led to the highest number of upregulated genes related to transcription factors, protein modification, indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellin acid (GA), receptor kinases, and Ascorbic acid/Glutathione (Ascorb/Gluath). UV-C might promote the accumulation of phenolic components by upregulating the expression of their biosynthesis related genes. UV-C may be an effective in vitro approach for improving the application value of waste grape berries by enhancing the accumulation of the nutritious phenolic components.